Torque-speed Characteristic of Split Winding Motor for Electric Vehicle - Zhuang Sen; Zhao Shuang (Jixie chuandong)
In order to use the dispersion of the battery in sub-box to establish a low voltage driving system,the conception of split winding motor is proposed,the theory of split winding and the method of winding split are elaborated in the example of a fractional slot concentrated BLDCM. Through the simulation analysis of the virtual fractional slot concentrated BLDCM,the practicability of the split winding motor is preliminarily confirmed. It’ s also found that when the torque-speed characteristic is consistent no matter the winding is split or not,the sum voltage of all the sub-winding is higher than the voltage before the winding is split.